Sublethal Effects of Imidacloprid on Bemisia tabaci (Hemiptera: Aleyrodidae) Under Laboratory Conditions - He, Yuxian; Zhao, Jianwei; Wu, Dongdong; Wyckhuys, Kris A.G; Wu, Kongming (Journal of economic entomology, 2011)
The sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), is one of the most important pests in tropical and subtropical agriculture and is a key pest in greenhouse production worldwide. Current management of B. tabaci relies upon frequent applications of insecticides. Insecticide use not only directly affects pest populations through acute toxicity but also has indirect (sublethal) effects on pest physiology or behavior. In this study, we described sublethal effects of imidacloprid on adult feeding, immature development, adult fecundity, and F1 development of B. tabaci. Honeydew excretion of adults feeding on leaves treated with LC20 and LC40 concentration was significantly lower than that on untreated leaf discs. Egg production of B. tabaci adults subject to LC20 and LC40 concentrations also was less than untreated individuals. Upon transfer to untreated leaves, honeydew excretion and egg production recovered well within 24 and 48 h, respectively. Exposure to LC20 and LC40 concentrations significantly affected developmental time of B. tabaci eggs and nymphs, whereas it did not affect adult molting rate. We did not find sublethal effects on longevity and fecundity of B. tabaci adults when exposed to LC20 and LC40 concentrations for 24 h, and on egg hatching rate, nymphal mortality, and molting rate of the subsequent F1 generation. Exposure to imidacloprid at LC40 concentration significantly decreased the number of females in the F1 generation. Imidacloprid negatively affects development and reproduction of exposed individuals, and sex ratio of subsequent (F1) generation of B. tabaci, which probably disrupts B. tabaci population dynamics, slows population increase, and reduces infestation levels. Therefore, it is necessary to consider potential impact from imidacloprid for integrated management of the pest.